Non-transient "self-sustaining" heparin-induced thrombocytopenia: 4-year persistence of a platelet-activating PF4/heparin–antibody status without heparin exposure. (December 2014) - Birschmann, Ingvild; Gummert, Jan; Schirmer, Uwe; Knabbe, Cornelius; Sachs, Ulrich J.; Koster, Andreas
Abstract The more we come to understand the pathophysiology of heparin-induced thrombocytopenia (HIT) syndrome, the more we realize that HIT is a rather unusual immune response. One peculiar feature of HIT is the transient character of the antibodies. After cessation of exposure to heparins, the antibodies tend to disappear after 40–100 days. If re-immunization occurs, it generally takes at least 4 days to redevelop antibodies (if they are formed at all). We report about a patient who most likely developed platelet-activating IgG-specific platelet factor 4 (PF4)/heparin antibodies after knee surgery, experienced a transient ischemic attack years later [when HIT was diagnosed by using PF4/heparin ELISA] and presented a high number of these antibodies even 4 years after this first diagnosis of HIT without further re-exposure to heparin.